196k views
5 votes
A. f(x) = x2 - 11x - 12

B.f(x) = x2 - 4x -12
C. f(x) = x2+x-12
D. f(x) = x2-x-12
Match each quadratic function given in factored form
with its equivalent standard form listed on the left.
f(x) = (x + 2)(x-6)
f(x) = (x - 4)(x+3)
f(x) = (x – 12)(x + 1)
f(x) = (x – 3)(x +4)

User Nograpes
by
6.1k points

2 Answers

6 votes

Answer:

x^2 -11x-12=(x-12)(x+1)\\x^2 -4x - 12 = (x-6)(x-+2)\\x^2+x-12 = (x-3)(+4)\\x^2-x-12=(x-4)(x+3)

Explanation:

User Rahma Samaroon
by
6.2k points
6 votes

Answer:


x^2 -11x-12=(x-12)(x+1)\\x^2 -4x - 12 = (x-6)(x-+2)\\x^2+x-12 = (x-3)(+4)\\x^2-x-12=(x-4)(x+3)

Explanation:

The sum of the two roots gives you the x term of the quadratic.

User Michael Wasser
by
6.6k points